Shear-Clinching of Multi-Element Specimens of Aluminium Alloy and Ultra-High-Strength Steel - Han, Daxin; Hörhold, Réjane; Müller, Martin; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (Key Engineering Materials, 2018)
The newly developed joining-by-forming technology "shear-clinching", features a potentially single-stage process for joining UHSS without requiring any additional elements. Foundational studies have focused on the functionality of shear-clinching at a one-element sample. To ensure the safety of the industrial application of the shear-clinching technology, an investigation with component-like samples with several joints is required. This paper presents a detailed analysis of the material behaviour during the shear-clinching process with multi-element specimens to evaluate the influence of the neighbouring joints. In order to describe the influence of the neighbouring joints, the deformations resulting from the bending and material displacement are recorded without contact after the joining process: locally around the joining point and globally over the entire sample size. To minimize such bending effects, a tool-sided adaptation is provided. The results show the high potential of shear-clinching joining by UHSS and give further recommendations for future multi-material application.
LFT Import::2019-07-29 (2302)
Keywords: Clinching; Joining by forming; Lightweight; Multi-element specimen; Multi-material mix